TYPOLOGY OF FEMALE CHARACTERS IN THE NOVELS OF WESTERN ARMENIAN FEMALE AUTHORS - Hambardzumyan, Naira; Parsadanyan, Siranush (Armenian Folia Anglistika, 2022)
The aim of the research is to explore the typology of female characters in the works of female writers Srbuhi Tyusab, Sipil and Zapel Yesayan in the context of social transformations in the Ottoman Empire of the second half of the 19th and the beginning of the 20th centuries. A comparative analysis of female characters in the novels Mayta (1883), Siranush (1884), Araksia or the Governess (1887) by Tyusab, A Girl’s Heart (1891) by Sipil, and Gardens of Silihtar (1935) by Zapel Yesayan has been attempted from the perspectives of literary and sociological studies. The data are analysed with the application of the graph-based semantic representation method. The actuality of the research lies in its interdisciplinarity, according to which mutual connections are created between literary studies, sociology and computer science. The selection of these works as research data is accounted for by their volume, variety of characters, simplicity of plots and little branching. All the main characters in all the novels are females. All the novels were written around the same time period (the 1880s-1900s) and bear characteristics of a romantic novel, except Zapel Yesayan’s autobiographical novel Gardens of Silihtar written in 1935. Despite the year the novel was written, in it Yesayan describes the same period (the end of the 19th century) reflected in Tyusab’s and Sipil’s novels.
Keywords: Srbuhi Tyusab; Sipil; Zapel Yesayan; graph-based semantic modeling; typological analysis; female characters; sociology